2017
DOI: 10.1016/j.bcp.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Platensimycin and platencin: Inspirations for chemistry, biology, enzymology, and medicine

Abstract: Natural products have served as the main source of drugs and drug leads, and natural products produced by microorganisms are one of the most prevalent sources of clinical antibiotics. Their unparalleled structural and chemical diversities provide a basis to investigate fundamental biological processes while providing access to a tremendous amount of chemical space. There is a pressing need for novel antibiotics with new mode of actions to combat the growing challenge of multidrug resistant pathogens. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 84 publications
1
76
0
Order By: Relevance
“…Since the discovery of PTM and PTN as promising antibiotics over a decade ago, these natural products have garnered considerable attention. Significant progress in understanding the biosynthetic pathways of 3 and 4 has been made through the use of microbial genomics 11 . Given the amount of time and resources spent on studying 3 and 4 , we were initially surprised to identify sulfur-containing congeners of PTM and PTN 8 , 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery of PTM and PTN as promising antibiotics over a decade ago, these natural products have garnered considerable attention. Significant progress in understanding the biosynthetic pathways of 3 and 4 has been made through the use of microbial genomics 11 . Given the amount of time and resources spent on studying 3 and 4 , we were initially surprised to identify sulfur-containing congeners of PTM and PTN 8 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…1a–c ) 8 . PTM and PTN were originally isolated from Streptomyces platensis MA7327 and MA7339, respectively, representing a class of promising natural product antibiotics that target bacterial and mammalian fatty acid synthases 9 11 . Structurally, they are comprised of two distinct moieties, a diterpene-derived lipophilic ketolide and a 3-amino-2,4-dihydroxybenzoic acid (ADHBA, 5 ), linked by an amide bond (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 PTM and PTN are potent inhibitors of bacterial fatty acid synthase (FASII) and are effective against a wide range of bacteria including methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococci (VRE), and Mycobacterium tuberculosis , while displaying no toxicity. 24 PTM is also a lead compound for the treatment of diabetes and related metabolic disorders as it is a potent and highly selective inhibitor of mammalian fatty acid synthase.…”
Section: Introductionmentioning
confidence: 99%
“…Lipids in the 10-lipid mixture used in this study belong to the following phytochemical families: terpenes (terpinyl acetate, guaiol, elemol, sabinene, thujopsene, totarol, b-pinene, and cembrene) and fatty acids: (palmitic acid and 9-octadecenamide). The components of C. obtusa lipid extract including terpinyl acetate (Devkota et al, 2008;Rudolf et al, 2017;Zhang et al, 2016), sabinene (Vimal et al, 2017), guaiol (Choudhary et al, 2007), cembrene (Chen et al, 2009), and totarol (Kubo et al, 1992) have been shown to have antibacterial activities. Guaiol (Liu et al, 2013) and b-pinene (da Silva et al, 2012) also have been shown to have antifungal activities.…”
Section: Discussionmentioning
confidence: 99%